2014
DOI: 10.1080/15226514.2013.810583
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Nutrient Supply on the Growth of Seven Bamboo Species

Abstract: Over the last decade, bamboo has emerged as an interesting plant for the treatment of various polluted waters using plant-based wastewater treatment systems. In these systems, nitrogen and phosphorous concentrations in wastewater can exceed plant requirements and potentially limit plant growth. The effects of two nutrient rates on the growth of seven bamboo species were assessed in a one-year experiment: Dendrocalamus strictus, Thyrsostachys siamensis, Bambusa tuldoides, Gigantochloa wrayi, Bambusa oldhamii, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…The C, N, and P content of aboveground bamboo components can be estimated accurately by allometric equations, with DBH accounting for 46%-81% of the variation in the C, N, and P content of the fertilized plots and with DBH accounting for 45%-85% in the C, N, and P content of the unfertilized plots (Table A1). This result is consistent with a previous study that demonstrated that allometric equations developed by DBH parameters provided reliable estimates of C contents of Moso bamboo [18]. However, the allometric equations in branches and leaves were not appropriate for the K, Ca, and Mg contents, having low coefficient of determination (r 2 ) values in allometric equations.…”
Section: Nutrient Content and Stocks Of Biomass Componentssupporting
confidence: 91%
See 3 more Smart Citations
“…The C, N, and P content of aboveground bamboo components can be estimated accurately by allometric equations, with DBH accounting for 46%-81% of the variation in the C, N, and P content of the fertilized plots and with DBH accounting for 45%-85% in the C, N, and P content of the unfertilized plots (Table A1). This result is consistent with a previous study that demonstrated that allometric equations developed by DBH parameters provided reliable estimates of C contents of Moso bamboo [18]. However, the allometric equations in branches and leaves were not appropriate for the K, Ca, and Mg contents, having low coefficient of determination (r 2 ) values in allometric equations.…”
Section: Nutrient Content and Stocks Of Biomass Componentssupporting
confidence: 91%
“…Similar results were observed in seven bamboo species in Reunion Island, with no significant increase in K concentration in leaves with increasing fertilization [18]. A previous study reported that K nutrients may be rapidly translocated from leaves for the growth of new tissues such as culm [18], since K nutrients in bamboo species are the most important element stored by bamboo components such as culm. However, in this study, the K nutrients may not be limited due to the high concentration of available soil K in both treatments (Table 2).…”
Section: Nutrient Concentrations Of Bamboo Componentssupporting
confidence: 82%
See 2 more Smart Citations
“…Among all bamboo species in China, the most substantial species is Phyllostachys edulis (moso bamboo), with more than three million hectares planted [9,10]. After emerging, the shoot of moso bamboo grows fast, and under suitable conditions, its growth rate could reach 1 m per day [11,12]. Therefore, different agroforest management practices, especially mineral fertilizer applications, have been used to stimulate moso bamboo growth [10][11][12].…”
Section: Introductionmentioning
confidence: 99%